Educational Game Activities from Natural Media to Promote Basic Skills Mathematics of Early Childhood - Boontrai, Suchira; Nakunsong, Tassanee (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Mathematics is an important tool related to human daily life. in learning other sciences Gaining experience in mathematics gives learners the ability to think. reasonably and used to solve various problems Well, basic mathematical skills are therefore very important as a basis for further learning. This research intended for 1) To develop educational game activities from natural media 2) to study the effectiveness index of educational game activities from natural media for elementary school children 3) to compare basic mathematical skills of early childhood children before and after organizing educational game activities from natural media. Methodology: The sample group used in this research were Kindergarten 2 students at Jitranon Kindergarten School. Private Education Promotion Office, Mahasarakham Primary Educational Service Area, Region 1, semester 2, the academic year 2022, 19 students were obtained by cluster random sampling. For kindergarten year 2 students. 2) The basic mathematics skills test for kindergarten year 2 students was a multiple-choice test, with 3 options, and 20 items. Statistics used in data analysis were mean percent, standard deviation, and t-test. Results: 1) the organization of educational game activities from natural media; to promote basic skills and mathematics of early childhood Efficiency was 80.0/85.0 according to the criteria. 2) The effectiveness index for educational game activities from natural media to promote basic skills in early childhood mathematics equals 0.6777 accounting for 67.77 percent, and 3) basic academic skills in early childhood mathematics After the educational game activities from natural media were higher than before the game activities. Natural media education is Statistically significant at the .05 level. Conclusion: Engaging in educational game activities using natural media effectively promotes fundamental mathematics skills in young children, meeting the specified criteria with an efficiency rating of 80.0/85.0. The effectiveness index is 67.77%, significantly enhancing basic mathematics skills statistically at the 0.05 level after such activities compared to pre-game educational media exposure.